Effects of therapeutic modalities on patients with post stroke shoulder pain - Moniruzzaman, M; Salek, KM; Shakoor, MA; Mia, BA; Moyeenuzzaman, M (Mymensingh Medical Journal, 2010)
Mymensingh Med J. 2010 Jan;19(1):48-53. The abstract of this article is available on the PubMed website